The Psychometric Properties of the Norwegian version of WHO Five Well-Being Index (WHO-5) - Kaiser, Sabine; Kyrrestad, Henriette (PsykTestBarn, 2019)
Description: WHO-5 was developed at the Mental Health Centre North Zealand in Hillerød, Denmark and published in 1998. WHO-5 was translated into Norwegian by Olaf Bakke in 2004. The translation process has not been documented. The WHO-5 does not require permission for use. It measures mental well-being, and has been used as an outcome measure in clinical trials and as a screening tool for depression. The WHO-5 can be used among children and adolescents aged nine years and older. The questionnaire consists of five questions and it takes approximately three minutes to answer. There are no requirements in terms of competence for administering the test or for interpretation of scores. Literature search: The literature search resulted in five included articles. These were cross-sectional, as well as RCT and pre-post studies, and included samples of children and adolescents aged 10-19 years. Two studies included the same sample of Norwegian and Danish adolescents (N = 294) who were sampled from their general practitioner patient lists. Three studies consisted of Swedish children and adolescents (N = 27-63) diagnosed with depressive disorders. Psychometric: One article reported mean and standard deviation, and one reported reliability. None of the included articles reported norms. Three of the articles reported predictive validity, sensitivity and specificity for the use of WHO-5 as a screening tool for depression. Conclusion: The Norwegian version of the WHO-5 does not have sufficient documentation to assess the quality of the test properties and the documentation from the Swedish studies is also limited. Therefore, more studies are needed to investigate the psychometric properties of WHO-5.